Analysis of the Development of Sports Intelligence From the Application of "Intelligent Robot Dogs" in Competitive Sports - Niu, Dandan (Technium Social Sciences Journal, 2023)
The 19th Asian Games, hosted in Hangzhou, China, have been described as a large-scale event of sports intelligence, with high-tech technology such as "digital torchbearers", autonomous buses, 5G information networks, meta-universes, and intelligent robots on show. This paper will use the "intelligent robot dog" as the research object and will use the literature method, case study method, logical reasoning method, and other research methods to describe the concepts of digitalization and intelligent robots and analyse the positive effects that the combination of sports and intelligence brings to sports competitions. Using the application of an intelligent robot dog in sports competition at the Hangzhou Asian Games as a starting point, this paper will analyse the current state of sports intelligence, present the problems encountered as well as the solutions, and finally forecast the future market development of the combination of sports and artificial intelligence applied in competitive sports.